Perancangan Sistem Informasi Stok dan Penjualan Obat Apotek Hanifa Menggunakan Java - Dhika, Harry; Sarwandianto, Achmad; Sari, Pramita (Jurnal Riset Informatika dan Inovasi, 2024)
Pharmacy as a means of health care, needs to prioritize the interests of the community and is obliged to provide, store and hand over pharmaceutical supplies of good quality and guaranteed accuracy. In drug data storage, it still uses the manual method which hinders the work process at the pharmacy into a computerized system. To overcome these problems, the design of the drug stock information system and sales was carried out in the Java Netbeans programming language using the MySQL database at the Hanifa Pharmacy. Making this system aims to facilitate the work process of employees at pharmacies so that data is stored accurately and makes it easier to access data reports on drugs, purchases, sales and returns. The research method used is Grounded Research and system development using the System Development Life Cycle (SLDC), while the data collection techniques use interviews, observation, and relevant literature studies. The result of this research is an information system on the supply, purchase, returns and sales of drugs which is expected to help simplify the process of drug supply and drug sales at the Hanifa Pharmacy.